1978
DOI: 10.1080/00380237.1978.10570307
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Relationship between Infant Mortality and Socioeconomic Status: 1950 and 1970

Abstract: The infant mortality/socioeconomic status relationship was examined in the city of Toledo, Ohio for the years center ing around 1950, 1960 and 1970. Data were obtained from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore, our conclusion is that the lack of an association between childhood health and adult socioeconomic status in older age groups is (partly) caused by a differential reporting bias. The established relationship in older generations between (Adamchak and Stockwell 1978, Antonovsky and Bernstein 1977, Brooks 1975, Clifford and Brennon 1978, Douglas 1964, Morris and heady 1955, Pamuk 1988, Woolf and Waterhouse 1945. This relationship was also found in the Netherlands (Van de Mheen et al 1996, Van Poppel 1982.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, our conclusion is that the lack of an association between childhood health and adult socioeconomic status in older age groups is (partly) caused by a differential reporting bias. The established relationship in older generations between (Adamchak and Stockwell 1978, Antonovsky and Bernstein 1977, Brooks 1975, Clifford and Brennon 1978, Douglas 1964, Morris and heady 1955, Pamuk 1988, Woolf and Waterhouse 1945. This relationship was also found in the Netherlands (Van de Mheen et al 1996, Van Poppel 1982.…”
Section: Discussionmentioning
confidence: 74%
“…To date this research has focused on the relationship between socioeconomic status, more specifically family income status, and levels of mortality during the first year of life. Thus far this relationship has been examined at four points in time centered on the decennial censuses of 1960, 1970, 1980, and 1990(Adamchak and Stockwell, 1979Stockwell and Goza, 1996a;Stockwell et al, 1987a). Those studies consistently revealed the presence of a strong and persistent inverse relationship between infant mortality and family economic status in metropolitan Ohio.…”
Section: Introductionmentioning
confidence: 95%
“…Infant and child mortality have long been regarded as sensitive indicators of differentials in social and economic well-being (Adamchak & Stockwell, 1978;Frenzen & Hogan, 1982;Haines, Avery & Strong, 1983). For while the general mortality level is strongly associated with socioeconomic development (Kitagawa & Hauser, 1973;Fuchs, 1974;Ruzicka, 1981;UN, 1982a), infant and early childhood (age 1-4 years) mortality is generally affected by parents' (especially mother's) socioeconomic status and mother's background characteristics (Wray, 1971;Caldwell, 1979;Arriaga, 1980b;Federici & Terrenato, 1980;Schultz, 1980;Rutstein, 1983;Gubhaju, 1984;Ruzicka, 1984).…”
Section: Introductionmentioning
confidence: 99%